DI DESA SUNGAI PINANG INDAH KECAMATAN KUBU BABUSSALAM KABUPATEN ROKANHILIR - Ratna Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Sungai Pinang Indah Village Kubu Babussalam Sub-District Rokan Hilir Regency. This research entitled "Puppies of Toddlers Children at Family Couples Married Early Age in Sungai Pinang Indah Village Kubu Babussalam Sub-district Rokan Hilir". The purpose of this research is to know the pattern of parenting of children under five in families of married couples early age in Sungai Pinang Indah Village. The focus of this research is the impact of early marriage on toddler pattern in Sungai Pinang Indah Village. Determination of the number of samples used by the authors in this study is by Purposive Sampling method as many as 3 parents who married at an early age based on data from the Office of Religious Affairs Kubu Babussalam District. Data instruments are observation, interview and documentation. Research conducted found that there are several patterns of child care that is applied by the family of married couples early age in the village of Sungai Pinang Indah is as follows: Permissive parenting pattern, Parenting emphasize what is done by children allowed parents, parents obey all children's wishes. Research subjects did not screen child behavior choices. Every child's will is obeyed as the child wishes. Democratic parenting, Parents and children can not do arbitrarily, children are trusted and trained to account for all his actions are not hypocritical and honest. Research subjects have attempted so that they can control children as much as possible. Authoritarian parenting, For parents who adopt authoritarian upbringing systems. Each child will be in shape according to what he wants, not based on what the child wants and the child can afford. Research subjects admitted pretty hard on his son. Children are often ignored with in-laws. So the child spent more time with his grandmother and grandfather.Keywords: Foster Pattern, Marriage, Early Age, Impact